Pelatihan Strategi Pemecahan Masalah Matematika Nonrutin Sebagai Persiapan KSN Matematika Di SMP Al Irsyad Purwokerto - Dwiani Listya Kartika; Dian Pratama; Noor Sofiyati (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2022)
The purpose of this service activity is to introduce, prepare and increase students' knowledge, especially students of mathematics achievement at SMP Al Irsyad Al Islamiyah Purwokerto about effective and efficient as a provision to take part in the National Science Competition in the field of mathematics or other similar math competitions. So far, the selected students are given independent guidance by the teachers at the school. However, due to scientific limitations and the teacher's busy schedule, the activity of building mathematics achievement is still not optimal. The method of implementing this activity consists of three stages starting with the first stage, namely the introduction of mathematical problem solving strategies, followed by the second and third stages in the form of material deepening activities. The post-test results showed an increase in the average post-test score of 22% from the average pre-test score. This shows an increase in the non-routine mathematical problem solving ability of the participants after being given training. The results of observing participant activities for three meetings also showed that the percentage of activity during the training increased at each meeting. This shows the increasing ability and motivation of the trainees in solving non-routine math problems. Keywords: Problem Solving, Non-routine Mathematics Problems, National Science Competition